(untitled) (Stavební obzor - Civil Engineering Journal, 2019)
In order to study on the vibration effect of the blasting in the upper and lower cross tunnels, depress the impact of blasting vibration on existing adjacent tunnel and acquire the sound way of tunnel blasting construction, the finite element software LS-DYNA was adopted to calculate what vibration effect of existing tunnel would be generated by the different detonation modes (simultaneous initiation and hole-by-hole initiation) and the different cut modes (parallel cut and oblique cut). In general, the results of numerical simulation compared with the results measured in real, they are generally consistent. Results show that the vibration velocity of hole-by-hole initiation of digital electronic detonator is 40% lower than ordinary simultaneous initiation of millisecond detonator, and the vibration acceleration is reduced by 24%. As regards vibration displacement, the distinction between the two detonation modes is small. The rule of velocity decay with increasing distance from the initiating position is similar in this two cases. Meanwhile, the vibration velocity of oblique cut is lower than parallel cut. But, for the vibration acceleration, the oblique cut is 15% higher than parallel cut. For oblique cut, the seismic waves show a pronounced periodicity and the energy is relatively concentrated. The fact is quite opposite when the parallel cut applied. In the case of explosion of hard rock strata, the effect of oblique cut is better than parallel cut.